Association Between Family Functioning and Depressive Symptoms Among Colombian High-School Adolescents - Reyes-Rojas, Monica; Campo-Arias, Adalberto; Caballero-Domínguez, Carmen (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2023)
The study aimed to estimate the correlation between family functioning and depressive symptoms among high-school adolescents in Santa Marta, Colombia. A cross-sectional study was done, which involved a sample of high-school students between 13 and 17 years old. Students completed the Family APGAR questionnaire that quantifies adaptation, participation, growth, affectivity, and problem-solving in the family context and the World Health Organization-5 Well-Being Index (WHO-5-WBI) quantifying depressive symptoms. Spearman (rs) correlations established the relationship between the Family APGAR item scores and the total WHO-5-WBI score. 1,462 students participated in the study (M = 15.98, SD = 0.82), and 60.33% were females. The correlations between the Family APGAR items and depressive symptoms scores were rs = 0.34 for adaptation, rs = 0.37 for participation, rs = 0.33 for growth, rs = 0.33 for affectivity, and rs = 0.38 for problem resolution, all with p-values < 0.01. In conclusion, the Family APGAR items correlated positively with depressive symptoms. Family functioning should always consider in studies that explore depressive symptoms in high-school students.